The blackbody radiation in a D-dimensional universes - Cardoso, Tatiana R. [UNESP]; Castro, Antonio S. De [UNESP] (Sociedade Brasileira de Física, 2005)
The blackbody radiation is analyzed in a universe with D spatial dimensions. Using the classical electrodynamics suited to the a D-dimensional universe and employing hyperspherical coordinates, the spectral energy density as well as the total energy density are calculated as function of the dimensionality of the universe. The Wien's displacement law and the Stefan-Boltzmann law are properly generalized.

A radiação de corpo negro é analisada em um universo com D dimensões espaciais. Usando a eletrodinâmica clássica consonante com a dimensionalidade do universo, e empregando o sistema de coordenadas hiperesféricas, tanto a densidade de energia espectral quanto a densidade de energia total são calculadas em função do número de dimensões espaciais. A lei do deslocamento de Wien e a lei de Stefan-Boltzmann são apropriadamente generalizadas.
A radiação de corpo negro em um universos D-dimensional
Keywords: blackbody; D-dimensions; extra dimensions; hyperspherical coordinates; corpo negro; D dimensões; dimensões extras; coordenadas hiperféricas